Indian Poplars with Special Reference to Indigenous Species - Naithani, H. B.; Chandra, Sumer; Pal, Mohinder (Indian Forester, 2001)
Genus Populus is usually dioecious, rarely monoecious viz. Populus lasiocarpa; exceptionally bisexual i.e. Populus jaquemontii var. glauca. There are only four species of Populus native to India viz. Populus ciliata, P. gamblei, P. jacquemontii var. glauca and P. rotundifolia. Rest all are exotic and some of them are naturalized in Kashmir i.e. P. alba, P. euphratica and P. nigra. A key to the identification of both wild and exotic species, nomenclature and distribution of species; work done on the endemic species and suggested lines of work have been provided for the improvement of indigenous species.